It is possible to consider that the unreliability is a naratological category? - Ceska, Jakub (Bohemica Olomucensia, 2013)
The paper deals with the question if it is possible to find the origin of extensive discussions about the unreliability in disagreement of contradictorical perspectives. The author tries to enlighten the thematisation of the notion unreability that indicates opposing theoretical perspectives.